Minimizing Microbial Food Safety Hazards for Fresh Fruits and Vegetables, Manures and Biosolids - Gast, Karen L. B.; Holt, Kim (My University, 2000)
This publication decribes the proper management of animal manure and muncipal biosolids around crops.
MF2483_2000_12
Keywords: MF2483; Health and Safety; fruits and vegetables; MF